Endorsing Sustainable Enterprises Among Promising Entrepreneurs: A Comparative Study of Factor-Driven Economy and Efficiency-Driven Economy - Sargani, Ghulam Raza; Jiang, Yuansheng; Zhou, Deyi; Chandio, Abbas Ali; Hussain, Mudassir; Khan, Nawab (Frontiers in Psychology, 2021)
Understanding business trails among promising aspirants may contribute to an actual motive for diminishing ecological tracks and escort to developing devotion toward deciding intentions across various entrepreneurial types and tiers solely from the sustainability domains. Therefore, this study endeavors to comprehend and seek to employ the Theory of Planned Behavior (TPB) to inspect the relationship between antecedents on sustainable enterprise intention and sustainable value creation. In this study, we used the convenience sampling method and the quantitative data of 1,070 respondents from Pakistan and China and applied a SmartPLS structural equation model and partial least square path modeling by mediational and multigroup analyses. Findings divulge that R2 (79.8%) value in the Pakistan sample of attitudes to sustainability, perceived entrepreneurial desirability (PED), and perceived entrepreneurial feasibility (PEF) was comparatively higher than in China. The R2 (75.6%) variance value on sustainable entrepreneurial intentions (SEI) was recorded higher in the Pakistani sample. However, the relationship of environmental values, self-efficacy, and extrinsic and intrinsic rewards show positive and significant mediational effects on both the economies of SEI. The findings disclosed an inconsistent character of extrinsic rewards, general self-efficacy, and job security depict negative significant impacts of aspirations on sustainable entrepreneurship (SE) among promising entrepreneurs on sustainability enterprises in both Pakistan and China. This study extends on existing entrepreneurship literature. Results supported the designed hypothesis and played a significant role in shedding light on an individual trait underpinning a career in a sustainable business start-up. The study looks at the issue from the viewpoint of sustainability domains. It seeks to determine the individual PED, PEF, and attitude toward sustainable entrepreneurship (ATSE) as the mediational variables. The study highlights the importance of work values in pursuing sustainability-oriented entrepreneurship programs for promising aspirants to improve their entrepreneurial skills and knowledge podium, which will encourage them to become sustainable future entrepreneurs. Furthermore, the study provides understandings for ratifying sustainable openings and debates the potential paths for sustainable business growth and opportunities among nascent entrepreneurs in both economies.